2019
DOI: 10.1002/biot.201800545
|View full text |Cite
|
Sign up to set email alerts
|

Towards Self‐Regulated Bioprocessing: A Compact Benchtop Bioreactor System for Monitored and Controlled 3D Cell and Tissue Culture

Abstract: Bioreactors are crucial tools for the manufacturing of living cell‐based tissue engineered products. However, to reach the market successfully, higher degrees of automation, as well as a decreased footprint still need to be reached. In this study, the use of a benchtop bioreactor for in vitro perfusion culture of scaffold‐based tissue engineering constructs is assessed. A low‐footprint benchtop bioreactor system is designed, comprising a single‐use fluidic components and a bioreactor housing. The bioreactor is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…A novel benchtop bioreactor was recently designed and tested in an article by de Bournonville et al (2019). The bioreactor was built to allow the user to control the internal environment as well as use it in a small space outside of clean room environments.…”
Section: Challenges and Future Perspectivementioning
confidence: 99%
“…A novel benchtop bioreactor was recently designed and tested in an article by de Bournonville et al (2019). The bioreactor was built to allow the user to control the internal environment as well as use it in a small space outside of clean room environments.…”
Section: Challenges and Future Perspectivementioning
confidence: 99%
“…For hPDCs we have already shown that this applies since process performance substantially increases in bioreactors [46]. In addition, data regarding cell growth could be either monitored online through imaging [47] or other sensors such as oxygen and lactate data [48], that once validated can provide more dense information throughout cell expansion [49] and not only during passaging. Especially with the development of fully controlled and sensorembedded bioreactor systems [50] such approaches could be embedded in control strategies, 'correcting' for donor dependent variation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, a novel, alternative intensified cell culture perfusion process resulted in a 2-fold volumetric productivity enhancement as compared to a commercially ready, optimized fed-batch process (Gagnon et al, 2019). In another study, a single-use fluidic components-based perfusion bioreactor system was developed and enabled the implementation of active environmental control (Bournonville et al, 2019). In a study by Bertrand et al (2019), the impact of perfusion cultivation on the intracellular physiological state of a CHO cell line was investigated, revealing decreased mAb productivity as well as a transition phase for metabolites and product quality before reaching steadystate conditions.…”
Section: Transgenic Animalsmentioning
confidence: 99%